Synthesis of Geopolymer from Inorganic Construction Waste - Pathak, Arbind; Jha, Vinay Kumar (Journal of Nepal Chemical Society, 2013)
Recently, the demolition of old houses and the construction of new buildings in Kathmandu valley are in the peak which in turn generates a huge amount of construction waste. There are two major types of construction wastes which are burden for disposal namely cement-sand-waste (CSW) and the coal fly ash (CFA). These construction wastes are rich source of alumino-silicate and thus used as raw material for the synthesis of geopolymer in this study. Geopolymers have been synthesized from CSW and CFA using NaOH-KOH and Na2SiO3 as activators. Some parameters like alkali concentration, amount of Na2SiO3 and curing time have been varied in order to improve the quality of geopolymeric product. The geopolymerization process has been carried out using 3-8M KOH/NaOH solutions, Na2SiO3 to CFA and CSW mass ratio of 0.25-2.00 and curing time variation from 5-28 days. The curing temperature was fixed at 40ºC in all the cases. 6M NaOH and 7M KOH solutions were found appropriate alkali concentrations while the ratio of sodium silicate to CSW and CFA of 0.5 and 1.75 respectively were found suitable mass ratio for the process of geopolymer synthesis. The maximum compressive strength of only 7.3 MPa after 15 days curing time with CSW raw material was achieved while with CFA, the compressive strength was found to be 41.9 MPa with increasing the curing time up to 28 days. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9334 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 45-51 Uploaded date: 12/16/2013